Spinal muscular atrophy with congenital bone fractures 2 caused by a rare loss‐of‐function ASCC1 gene mutation in two Bulgarian Roma patients. Issue 1 (26th March 2022) - Bradinova, Irena; Andonova, Silvia; Vazharova, Radoslava; Tomova, Stiliyana; Balabanski, Lubomir; Savov, Alexey
Abstract :